Synergistic interactions between anammox and dissimilatory nitrate reducing bacteria sustains reactor performance across variable nitrogen loading ratios - White, Christian; Antell, Edmund; Schwartz, Sarah L.; Lawrence, Jennifer E.; Keren, Ray; Zhou, Lijie; Yu, Ke; Zhuang, Weiqin; Alvarez-Cohen, Lisa (Frontiers in Microbiology, 2023)
Anaerobic ammonium oxidizing (anammox) bacteria are utilized for high efficiency nitrogen removal from nitrogen laden side-streams in wastewater treatment plants. The anammox bacteria form a variety of competitive and mutualistic interactions with heterotrophic bacteria that often employ denitrification or dissimilatory nitrate reduction to ammonium (DNRA) for energy generation. These interactions can be heavily influenced by the influent ratio of ammonium to nitrite, NH4 + :NO2 -, where deviations from the widely acknowledged stoichiometric ratio (1:1.32) have been demonstrated to have deleterious effects on anammox efficiency. Thus, it is important to understand how variable NH4 + :NO2 -ratios impact the microbial ecology of anammox reactors. We observed the response of the microbial community in a lab scale anammox membrane bioreactor (MBR) to changes in the influent NH4 + :NO2 -ratio using both 16s rRNA gene and shotgun metagenomic sequencing. Ammonium removal efficiency decreased from 99.77±0.04% when the ratio was 1:1.32 (prior to day 89) to 90.85±0.29% when the ratio was decreased to 1:1.1 (day 89 to 202) and 90.14±0.09% when the ratio was changed to 1:1.13 (day 169 to 200). The overall nitrogen removal efficiency (NRE) remained relatively unchanged (85.26±0.01% from day 0-89, compared to 85.49±0.01% from day 89-169, and 83.04±0.01% from day 169-200). When the ratio was slightly increased to 1:1.17-1:1.2, (day 202 to day 253) the ammonium removal efficiency increased to 97.28±0.45% and the NRE increased to 88.21±0.01%. Analysis of 16s rRNA gene sequences demonstrated increased relative abundance of taxa belonging to Bacteroidetes, Chloroflexi, and Ignavibacteriae. The relative abundance of Planctomycetes, the phylum to which anammox bacteria belong, decreased from 77.19% at the beginning of the experiment to 12.24% by the end of the experiment. Analysis of metagenome assembled genomes (MAGs) indicated increased abundance of bacteria with nrfAH genes used for DNRA after the introduction of lower influent NH4 + :NO2 -ratios. The high relative abundance of DNRA bacteria coinciding with sustained bioreactor performance indicates a mutualistic relationship between the anammox and DNRA bacteria. Understanding these interactions could support more robust bioreactor operation at variable nitrogen loading ratios.